2019
DOI: 10.3389/fpsyg.2019.00494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Early Postnatal Music Intervention on Cognitive and Emotional Development in Preterm Children at 12 and 24 Months: Preliminary Findings

Abstract: Preterm birth is associated with a higher prevalence of neurodevelopmental deficits. Indeed, preterm children are at increased risk for cognitive, behavioral, and socio-emotional difficulties. There is currently an increasing interest in introducing music intervention in neonatal intensive care unit (NICU) care. Several studies have shown short-term beneficial effects. A recent study has shown that listening to a familiar music (heard daily during the NICU stay) enhanced preterm infants’ functional connectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 75 publications
6
62
0
1
Order By: Relevance
“…Eighteen eligible studies 48 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 with 18 effect sizes on measures of intensified or deliberate orienting to an object were included ( Figure 4 ). Preterm birth was associated with diminished focused attention (Cohen d , −0.28; 95% CI, −0.45 to −0.11; z , −3.25; P = .001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen eligible studies 48 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 with 18 effect sizes on measures of intensified or deliberate orienting to an object were included ( Figure 4 ). Preterm birth was associated with diminished focused attention (Cohen d , −0.28; 95% CI, −0.45 to −0.11; z , −3.25; P = .001).…”
Section: Resultsmentioning
confidence: 99%
“…During the past 50 years, a myriad of studies assessed the association between preterm birth and attention development in early life, but only a few reviews attempted to synthesize and generalize the findings. 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 Two notable reviews 83 , 84 from previous decades suggested that infants born preterm show less-optimal attention performance. However, because both reviews were nonsystematic and did not attempt a statistical synthesis, there was a necessity for a methodical review to revisit the important claims of the previous s...…”
Section: Introductionmentioning
confidence: 99%
“…In addition, qualified music therapists ought to use the reference guidelines necessarily to consider appropriate intervention time, frequency, and duration of music therapy (Robb et al, 2011). In recent years, more researchers have observed and studied the long brain function of preterm infant (Filippa et al, 2017), neural development (Detmer et al, 2020;Haslbeck &Bassler, 2018;Haslbeck et al, 2017), cognitive and emotional development (Lejeune et al, 2019), etc. Hopefully, more meaningful studies focusing on the long-term effects of music therapy will be published in future.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Such science is also suitable to be part of an integrated approach when combined with other types of treatments, such as Kangaroo Mother Care, infant massage, and gentle handling [ 34 ]. Music therapy proven beneficial effects are evident in the short term, but further longitudinal studies are needed to confirm these findings, particularly for the infant’s neurodevelopment [ 35 ].…”
Section: Music Therapymentioning
confidence: 99%